Understanding the Challenges of the Halal Frozen Foods Distribution Channel in the ABC Industry - Kafi, Abdul; Zainuddin, Nizamuddin; Mohd Yusoff, Yuhainis; Deraman, Norita (2023)
The research case examines the significance of distribution channel preferences in today's dynamic business landscape. Given the rapid changes across industries, the optimization of transport systems is progressively gaining importance. The aim of this research is to understand the uneven dispersion of educational resources by analyzing the decision-making process concerning distribution models in the ABC industry. Employing a problem-solving approach, the case study actively engages students in addressing tangible issues, evaluating the advantages and disadvantages, and contemplating the broader impacts on supply chain effectiveness and customer satisfaction. The results indicate that the company is experiencing high market growth and holds a strong competitive position. However, in order to safeguard against distribution challenges and capitalize on opportunities in the ever-changing business landscape of the ABC industry, the company needs to enhance its distribution channels.